Myosin-dependent contractile activity of the actin cytoskeleton modulates the spatial organization of cell–cell contacts in cultured epitheliocytes - Krendel, M. (The National Academy of Sciences, 1999)
The spatial organization of cell–cell adherens junctions is distinct in cultured cells from two different tissue types, specifically, epitheliocytes and fibroblasts. In epitheliocytes, contacts are localized tangentially, along contacting cell edges and in association with circumferential actin bundles. Contacts between fibroblasts are radially oriented; that is, they are perpendicular to the overlapping edges of the cells and are associated with straight bundles of actin filaments. In the present study, we establish that the spatial organization of cell–cell contacts in the epithelial cell line IAR-2 can be converted from the typical tangential pattern to the radial pattern observed in fibroblasts. This transition can be induced by treatment with two agents, phorbol 12-myristate 13-acetate and nocodazole, which have different modes of action. Inhibition of myosin contractility reverses tangential-to-radial conversion of cell–cell contacts. These data suggest that formation of radially aligned contacts depends on modulation of contractility within the actin cytoskeleton through the myosin motor protein. The results open the possibility that modulation of the spatial organization of cell–cell contacts may play important roles in regulating organization and physiological functions of epithelial tissues.